A Correlation of Asthma with Ammonia Exposure and Other Risk Factors among Informal Workers of Poultry Farmers - Arriz Akbar Sukadi; Dewi Sumaryani Soemarko; Faisal Yunus (The Indonesian Journal of Community and Occupational Medicine, 2021)
Objective: To determine the prevalence of asthma and its corelation with ammonia exposure among informal workers of poultry farmers.Method: This study design was a cross-sectional analytic to 69 respondents using questionnaires, field observation, physical examination, spirometry measurement, and peak flowmeter test to diagnose work-related asthma and measurement of ammonia level in air environment of farm. All variable were bivariate tested by using Chi-square test or Fischer test. The variables which have p value <0,25 were included into multivariate analysis by using binary logistic regression.Results: The prevalence of asthma in poultry farmers was 21,74%. In bivariate analysis, there was a significant corelation between working periode (p = 0,035 with OR = 7,00) and smoking habit (p = 0,018 with OR = 5,603) with asthma. There was no significant corelation between age, sex, nutritional status, work location, education level and marital status with asthma. The result of measurement of ammonia level in the poultry farm enclosure on average is 2,329 ppm. Multivariate analysis was performed on several risk factors that fulfilled the requirement p <0,25 ie working periode, smoking habit, nutritional status, and work location. From the results of mutivariate found that workers with a history of smoking habits have the strongest corelation p = 0,013 with OR 17,305.Conclusion: The prevalence of asthma in poultry farmers was 21,74%. There was no significant corelation between ammonia exposure in the work environment with asthma. But there was a significant corelation between working periode and smoking habit with asthma.